(untitled) (Linguostylistic Studies, 2016)
The article highlights the issue of functional-stylistic heterogeneity and considers it as one of the most important differentiating features of epistolary text. The author argues that functional-stylistic heterogeneity is most clearly actualized in the Lesia Ukrainka’s letters and determines the uniqueness of her individual style. The study reveals main functional manifestations of heterogeneity and its explication in the lexical-semantic domain of this type of texts which include, first of all, various elements of scientific, business, religious, colloquial and artistic discourse. The emphasis is laid on the factors that influence the heterogeneity of the stylistic elements reflected in epistolary dialogues of the poetess with different addressees and on the typical manifestations of text inhomogeneity which determine the peculiarity of the individual interdiscoursiveness of Lesia Ukrainka’s letters. The author concentrates on the explication of the actual stylistic, genre and lexical-semantic varieties of heterogeneity. Key words: heterogeneity, epistolary text, letter, text, genre, intertextuality. References